‘N REGSFILOSOFIESE SOEKE NA POLITIEKE GEOORLOOFDHEID: DIE SPANNING TUSSEN PROSEDURE EN SUBSTANSIE (The Pretoria Student Law Review, 2021)
This article examines the conflict between procedure and substance. Substance should be favoured above procedure because where substance is at the heart of a legitimacy mechanism, collective decision-making can take place that makes a positive contribution and constructs an ethical society. Lawfulness and morality should be connected to give practical effect to such a model. Apartheid laws were collective decisions that were procedurally lawful, but were morally unsatisfactory. When a citizen faces a law that is immoral, and in terms of Aquinas irrational, it is not a law at all, and it should be resisted.